Models of Synodality of the Church in Indonesia - Utama, Ignatius L. Madya (Asian Horizons, 2025)
Synodality of the Church takes place when its members journey together, gather in assembly and take an active part in her evangelizing mission, and journey together with the entire human family. This understanding of synodality has been put into practice by the Churches in Indonesia through structure, leadership, as well as events and process. Parishes in Indonesia are structured into Lingkungan (Basic Ecclesial Communities). Leadership in the level of parishes and dioceses is carried out by parish pastoral council and diocesan pastoral council, which comprise of ordained and non-ordained members. Their main responsibilities are to formulate Guidelines for Pastoral Ministries for the parish and the diocese. These Guidelines pay attention to the situations of the nation and the country in order to be able to respond to them. At the national level synodality is expressed in the plenary assembly of the Bishops’ Conference as well as its annual meeting. All decisions at the Lingkungan, parishes, dioceses, the plenary assembly of the Bishops’ Conference and the annual meeting are made using local wisdom, musyawarah untuk mencapai mufakat (deliberation to arrive at consensus). The Indonesian Catholic Churches also journey together with Indonesian Protestant Churches through two collaborations: the issuance of joined Christmas pastoral letters as well as joined translation and publication of the Bible. Synodality requires leaders who have deep knowledge of Church’s teachings. There are three challenges: how to attract more young people to get involved, regeneration of leaders of the Lingkungan, and helping young priests to understand their responsibilities as educators in faith and defenders of the common good.